2009
DOI: 10.1002/jso.21383
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of thymidylate synthase at the protein, mRNA, and DNA levels as prognostic markers in colorectal adenocarcinoma

Abstract: TS genotyping on paraffin-embedded fixed tissues proved to be the most useful method for prediction of outcome of 5-FU treatment in patients with colorectal adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…2C). Additionally, several colorectal biomarkers, including Kirsten rat sarcoma viral oncogene homolog (KRAS), v-raf murine sarcoma viral oncogene homolog B (BRAF) (17), TS, DPD (18), SMAD family member 4 (SMAD4) (19) and most ColoPrint reference genes (8), including multiple C2 domains, transmembrane 1 (MCTP1), cathepsin C (CTSC) and pyridine nucleotide-disulphide oxidoreductase domain 1 (PYROXD1), were in group B, indicating the reliability and reproducibility of these genes for molecular analyses in colorectal cancer. Of note, however, one ColoPrint-related gene, hydroxy-δ-5-steroid dehydrogenase, 3β- and steroid δ-isomerase 1 (HSD3B1), had a wide expression distribution among the time-points.…”
Section: Resultsmentioning
confidence: 99%
“…2C). Additionally, several colorectal biomarkers, including Kirsten rat sarcoma viral oncogene homolog (KRAS), v-raf murine sarcoma viral oncogene homolog B (BRAF) (17), TS, DPD (18), SMAD family member 4 (SMAD4) (19) and most ColoPrint reference genes (8), including multiple C2 domains, transmembrane 1 (MCTP1), cathepsin C (CTSC) and pyridine nucleotide-disulphide oxidoreductase domain 1 (PYROXD1), were in group B, indicating the reliability and reproducibility of these genes for molecular analyses in colorectal cancer. Of note, however, one ColoPrint-related gene, hydroxy-δ-5-steroid dehydrogenase, 3β- and steroid δ-isomerase 1 (HSD3B1), had a wide expression distribution among the time-points.…”
Section: Resultsmentioning
confidence: 99%
“…The Response Evaluation Criteria in Solid Tumors (RECIST) were used to evaluate the patients' response following completion of the six cycles of chemotherapy. 1,2 No patient achieved a complete response (CR); 13 patients achieved partial responses and were included in the experimental group, six patients achieved stable disease, and 11 patients had disease progression (PD) and were included in the control group (see Table 1). …”
Section: Subjectsmentioning
confidence: 99%
“…Certain previous studies revealed no association between TS expression and the response to pemetrexed, whereas other studies revealed that low TS expression was associated with a high sensitivity to pemetrexed-based chemotherapy (2527); a meta-analysis favored the latter in NSCLC (7,18). It has also been reported that IHC more accurately predicts the response rate of pemetrexed compared with RT-qPCR, probably because TS protein, but not TS mRNA, exerts activity on DNA synthesis (28). In the present study, the tumors that were sensitive to pemetrexed on performing the CD-DST analysis revealed a slightly higher IHC score for TS compared with those without the sensitivity (P=0.217).…”
Section: Discussionmentioning
confidence: 99%